'Colidextribacter massiliensis' gen. nov., sp. nov., isolated from human right colon. (May 2017) - Ricaboni, D.; Mailhe, M.; Cadoret, F.; Vitton, V.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of 'Colidextribacter massiliensis' strain Marseille-P3083 T (CSURP3083), which was isolated from a human right colon lavage sample.